A review of alternatives to fenthion for quelea bird control. (February 2019) - Cheke, Robert A.; El Hady Sidatt, Mohamed
Abstract: The red-billed quelea ( Quelea quelea ) is the most important avian pest of small grain crops in semi-arid zones of Africa. Fenthion, an organophosphate, is the main avicide used for controlling the pest but it is highly toxic to non-target organisms. The only readily available pesticide that could replace fenthion is cyanophos, but this chemical is also highly toxic to non-target organisms, although less so than fenthion, and may be more expensive; however, more research on its environmental impacts is needed. Apart from chemical avicides, the only rapid technique to reduce the numbers of quelea substantially is the use of explosives combined with fuel to create fire-bombs but these also have negative effects on the environment, can be dangerous and have associated security issues. The technique is labour intensive and in practice can only be deployed against small (<5 ha) colonies and roosts. An integrated pest management (IPM) approach is the most environmentally benign strategy but, apart from when circumstances permit cultural control measures, most IPM activities only have realistic chances of succeeding in controlling quelea in small (<10 ha) areas. For instance, mass-trapping, which also has the advantage of providing a food source, is suitable when quelea roosts and colonies are less than 5 and 10 hectares in area, respectively. Nevertheless with both traps and mist nets, care is needed to minimise non-target casualties. Other IPM measures are also reviewed and the advantages and disadvantages of different methods tabulated. A related figure provides a decision tree for choosing appropriate measures for different circumstances. If fenthion has to be used, means of minimising its use include ensuring that spraying is only conducted when crops are threatened and that the lowest dosages necessary are applied. Regular training of pest control workers in how to use equipment correctly and in what to do in the case of accidental contamination of operators, and training of farmers on IPM principles and quelea biology through farmer field schools are recommended. Graphical abstract: Image 1 Highlights: Alternatives to the organophosphate fenthion to control quelea birds that minimise environmental damage are reviewed, including trapping techniques, harvesting birds for food, cultural control techniques and bird-scaring methods. Cyanophos, another organophosphate, and use of explosives both have severe environmental consequences. Procedures to minimise environmental damage when fenthion is used are recommended.